$$f(x) = \sum_{n=0}^{\infty} \frac{x^{2n+1}}{(2n+1)!}$$

Since we know that $ \frac{1}{2}(\exp(x) - \exp(-x)) $ is same as $$\frac{1}{2}\left(\sum_{n=0}^{\infty}\frac{x^{n}}{n!} - \sum_{n=0}^{\infty}\frac{(-x)^{n}}{n!}\right)$$

we can place our $f(x)$ in this form. But first we can do more simplifying, we can write that form as $\displaystyle \frac{1}{2}\sum_{n=0}^{\infty}\frac{x^{n}-(-x)^n}{n!}$. In my book I found next steps, we are placing our $f(x)$ in this last form and we get $$\frac{1}{2}\left(\sum_{n=0}^{\infty}\frac{x^{2n+1}-(-x)^{2n+1}}{(2n+1)!} + \frac{x^{2n}-(-x)^{2n}}{(2n)!}\right)$$

The part which I don't understand is, from where do we get that $\displaystyle\frac{x^{2n}-(-x)^{2n}}{(2n)!}$ ?

  • 1
    $\begingroup$ Well, $$\frac{1}{2}\sum_{n=0}^{\infty}\frac{x^{n}-(-x)^n}{n!}=\sum_{n=0}^{\infty}\frac{1-(-1)^n}{2}\frac{x^{n}}{n!}$$ right? So all there is to do is to compute $$\frac{1-(-1)^n}{2}$$ for every $n$. Can you do that? $\endgroup$ – Did Nov 17 '16 at 10:48

They split the sum in an even and an odd part. In general

$$ \sum_{n = 0}^{+\infty} a_n = \sum_{n=0,\;n\; {\rm even}}^{+\infty}a_n + \sum_{n=0,\;n\; {\rm odd}}^{+\infty}a_n = \sum_{n=0}^{+\infty}a_{2n} + \sum_{n=0}^{+\infty}a_{2n+1} $$

This is particularly useful here because $1-(-1)^{2n} = 1-1 = 0$ and $1 -(-1)^{2n+1} = 1 + 1 = 2$.

So your expression becomes

\begin{eqnarray} \frac{1}{2}\left(\sum_{n=0}^{+\infty}\frac{x^n}{n!} + \sum_{n=0}^{+\infty}\frac{(-1)^nx^n}{n!}\right) &=& \frac{1}{2}\sum_{n=0}^{+\infty}\frac{(1 -(-1)^n)x^n}{n!} \\ &=& \frac{1}{2}\sum_{n=0}^{+\infty}\frac{(1 -(-1)^{2n})x^{2n}}{(2n)!} + \frac{1}{2}\sum_{n=0}^{+\infty}\frac{(1 -(-1)^{2n+1})x^{2n+1}}{(2n+1)!} \\ &=& 0 + \frac{2}{2}\sum_{n=0}^{+\infty}\frac{x^{2n+1}}{(2n+1)!}\\ &=& \sum_{n=0}^{+\infty}\frac{x^{2n+1}}{(2n+1)!} \end{eqnarray}


For $n\in\mathbb N$, you have two cases:

  1. $n$ is odd. Then, $n=2k+1$ for some $k=0,1,2,\dots$
  2. $n$ is even. Then, $n=2k$ for some $k=0,1,2,\dots$

Hence, $\exp(x)-\exp(-x)$ can be written as (LHS) \begin{align}\sum_{n=0}^{\infty}\frac{x^{n}-(-x)^n}{n!}&=\sum_{n \text{ odd}}^{\infty}\frac{x^{n}-(-x)^n}{n!}+\sum_{n \text{ even}}^{\infty}\frac{x^{n}-(-x)^n}{n!}\\[0.3cm]&=\sum_{k=0}^{\infty}\frac{x^{2k+1}-(-x)^{2k+1}}{(2k+1)!}+\sum_{k=0}^{\infty}\frac{x^{2k}-(-x)^{2k}}{(2k)!}\\[0.3cm]&=\sum_{k=0}^{\infty}\frac{x^{2k+1}+x^{2k+1}}{(2k+1)!}+\sum_{k=0}^{\infty}\frac{x^{2k}-x^{2k}}{(2k)!}=\sum_{k=0}^{\infty}\frac{2x^{2k+1}}{(2k+1)!}\end{align}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.